Usage of Dockers in Networking: A Survey - Naveen, D.; Khavya, K. (Indian Journal of Computer Science, 2019)
Docker is an open source software platform that is used to create, deploy, and manage virtualized applications on containers that share a common operating system. The docker services are more powerful and can be integrated with the network to increase their efficiency. Dockers have inbuilt networking drivers and can be used in various types of networking such as host, bridge, and containers. In this paper, the survey of different papers that used docker in networking applications which increased their performance are listed and discussed. Mostly, the Kubernetes is taken as an example which is implemented in virtual environment and various networking clusters and cluster containers are discussed.